Lázár - Biedermann, Nelio (Summit Books, 2026)
"At the turn of the 20th century, the Lázárs welcome their newest member in their rural summer estate, surrounded by a menacingly dark, enchanting forest. Lajos von Lázár is a baby boy with translucent skin and light-blue eyes who looks nothing like the rest of his family. Sándor, the imposing patriarch, is ashamed of his son's peculiarity. Ilona finds her baby brother quite ugly. Mária is terrified that her son's uncanny resemblance to the stagehand who died a couple weeks earlier might spell disaster. While Imre, Sándor's brother whose otherworldly foresight is often confused for insanity, is struck by visions of a great catastrophe. Lajos's birth is emblematic of the many secrets, affairs, and peculiar otherworldly happenings that plague the Lázárs. As the decades go by, they will continue to fall prey to their desires, leading grand lives, and experiencing even greater tragedies as they're swept by the tides of war and revolution that befall their country. But time and again, in the lighter years, extraordinary love and hope shine through."--